Analysis of Needs for Development of MOOCs-Based Digital Module to Increase Concept Understanding of Junior Students on The Matter of Breathing Systems - Setiyowati, Indah (CV. Media Inti Teknologi, 2022)
The purpose of this study was to analyze the needs of students in using MOOCs-based digital learning media for understanding concepts in junior high school students. The subjects of this research were 20 students of class VIII of SMPN 11 Bengkulu City. This research is a Research and Development or RnD research. The research instruments used are interview guidelines, observation sheets, and learner needs questionnaires. The results obtained are in the form of observation data, interviews with one of the science subject teachers, and questionnaires filled out by research subjects. data analysis techniques used in this study are using qualitative and quantitative techniques.